Detection of knee chondral defect by 3-dimensional water selective for cartilage sequence (3d watsc) in 3.0 t magnetic resonance imaging - Ghazali, Fattah Rahiman (2021)
Knee chondral defect is one of the important causes of pain and disability. Arthroscopy is the gold standard method in detecting knee chondral defects however it is invasive. Magnetic resonance imaging (MRI) had been used as a non-invasive method in detecting knee chondral defect. Many MRI sequences had been developed for assessing the cartilage however it still pose limitations and inconsistent results. To date there is no general consensus for the MRI sequence in cartilage assessment. This study aims to assess the detection and grading of knee chondral defect in 3.0 T MRI using 3-dimensional water selective for cartilage (3D WATSc) sequence, in comparison with proton density (PD) sequence and gold standard arthroscopy. This retrospective study was conducted in Hospital Universiti Sains Malaysia (HUSM), Kelantan, from January 2017 until June 2020. MRI images of PD and 3D WATSc sequences of patients who fulfilled the inclusion criteria were independently reviewed by two independent raters. Presence of chondral defect and the grading in these two sequences were recorded and compared with arthroscopy findings. The interclass correlation coefficient (ICC) using absolute agreement under two-way mixed model for the grading between two raters was performed to determine the inter-observer reliability, which showed good inter-observer reliability for the grading of knee chondral defect in PD and 3D WATSc. Wilcoxon signed ranks test was used to test the differences in grade between PD and 3D WATSc. Sensitivity, specificity and accuracy were calculated for PD and 3D WATSc grades using the arthroscopy grades as standard reference. Total of seventy subjects (n=70), predominantly male (53 males; 17 females) with a mean age of 29.59 years old (15-44) were included in this cross-sectional study. The prevalence of knee chondral defect detected by PD, 3D WATSc and arthroscopy were 55.7 %, 48.6 % and 44.3 %, respectively. Majority of subjects were rated as Grade 0 across all assessment modalities with significant portion of subjects were rated as Grade II, Grade III and Grade IV. No statistically significant in the difference of knee chondral defect gradings between PD and 3D WATSc (p>0.05). The sensitivity, specificity and accuracy of 3D WATSc were 77 %, 74 % and 76 %, and PD were 64 %, 81 % and 71 %, respectively. The study showed that the diagnostic performance of 3D WATSc is not superior to PD in the detection of presence and grading of the knee chondral defect by 3.0 T MRI. The sequence also only had moderate sensitivity, specificity and accuracy as compared to gold standard arthroscopy. Therefore it cannot outperform PD sequence in assessing the knee chondral defect. Future prospective study is needed to further evaluate the diagnostic accuracy of 3D WATSc in 3.0 T MRI.